Plan de negocio para una empresa productora de jugo de caña en empaque, en la ciudad de santa marta y el corregimiento de Palomino en Dibulla la Guajira (2021)
The creation of industrial companies must conceive the structuring of a comprehensive value management plan for the implementation of processes aimed at ensuring quality logistics schemes, implementing technical models that are supported by a real capacity to respond to the requirements of the customer, and based on internal provisions on specialized machinery and operational labor. This business plan defines a design work for the future start-up in the city of Santa Marta of a company that processes sugarcane juice in PET-type packaging, for which a value proposition characterized by three components has been integrated macros: a commercial component evaluated in the market study, a technical-operational component evaluated in the technical study and an economic-financial component evaluated in the financial study. The general conclusion is that this business is highly feasible taking into account the assumptions handled, for this it is pertinent to follow the planned work plan in terms of studies and general requirements. At a methodological level, this project welcomes an applied research orientation since a functional proposal is designed taking into account some basic requirements. For this, theory related to the subject under study is used, and a final proposal is designed that solves specific social needs, making use of the scientific method through a previous process of observation and analysis of primary and secondary tools; According to the methodical deepening, an exploratory model is used, seeking an approach to the investigative event, and a quantitative recognition framework is carried out regarding the treatment of direct data.